QRICH1, as a key effector of endoplasmic reticulum stress, enhances HBV in promoting HMGB1 translocation and secretion in hepatocytes - Ying Feng; Yucai Geng; Zhixiang Liu; Lin Lu; Chen Cai; Chenke Ding; Shuyu Dong; Bo Gao (Immunobiology)
Background: Extracellular high mobility group box 1 (HMGB1) serves as a damage-associated molecular pattern (DAMP) and leads to diverse biological effects, including the aggravation of HBV-related liver diseases. However, mechanisms underlying HMGB1 secretion in HBV-induced hepatic injury and fibrosis remain unclear. Glutamine-rich 1 (QRICH1) is known as a critical effector of endoplasmic reticulum (ER) stress and is elevated in liver diseases. Whether QRICH1 participates in HBV-induced hepatic fibrosis warrants further investigation. Here, we explore the mechanism of HMGB1 secretion during HBV-induced hepatic fibrosis and the effect of QRICH1 on the process. Methods: In vivo experiments were conducted using a chronic recombinant cccDNA (rcccDNA) mouse model. Clinical specimens were obtained from Zhongshan Hospital, Fudan University. The levels of QRICH1 and HMGB1 were determined via immunohistochemistry. Liver collagen deposition was determined by Sirius red and Masson's trichrome staining. The serum levels of HMGB1 and indicators of liver injury were detected via ELISA. HMGB1 cyto-translocation was analyzed by Western blotting and quantitative real-time PCR (qRT-PCR). Results: Our findings demonstrated that ER stress promoted HBV-induced hepatic fibrosis in a mouse model. QRICH1 expression and HMGB1 secretion were elevated and positively correlated in rcccDNA mice with ER stress activation and chronic hepatitis B (CHB) patients with severe fibrosis. HBV modulated Sirtuin6 (SIRT6) expression, affecting HMGB1 cyto-translocation via acetylation regulation. Furthermore, QRICH1 enhanced HBV-induced HMGB1 translocation and secretion by regulating HMGB1 transcription. Conclusion: HBV promotes HMGB1 acetylation and cyto-translocation by modulating SIRT6 expression. QRICH1 enhances HBV-induced HMGB1 translocation and secretion by regulating HMGB1 transcription.